Liderazgo de servicio basado en el intercambio de conocimientos: el papel mediador de la motivación del servicio público y responsabilidad social corporativa en el Patronato Municipal de Amparo Social del GAD Latacunga. - Veloz Malavé, María Esther (2023)
The objective of the study was to analyze the mediating effects of public service motivation (PSM) and its relationship with servant leadership, knowledge exchange, and corporate social responsibility in public employees of the Municipal Board of Social Protection of GAD Latacunga. The study had a quantitative approach, since statistical instruments of a descriptive and inferential level were used with the purpose of knowing the response of public servants, it also had a bibliographic and field modality. The study sample consisted of 96 officials. After that, with the results obtained, a factor analysis was carried out and finally, the development of the activities whose purpose was to propose a plan to improve servant leadership, knowledge exchange, public service motivation, and the social responsibility of the entity. . It was concluded that the CSR component obtained a percentage of 76%, therefore, it has proven to be the most influential in internal organizational management. While service motivation scored 69%, suggesting that employees and leaders are strongly motivated by a sense of purpose and a willingness to serve the community. Finally, the institutional leadership factor obtained a percentage of 44% so, although it has a lower score compared to CSR, it is still a significant factor, this indicates that LI has an impact on internal organizational management.